2007
DOI: 10.1002/art.22213
|View full text |Cite
|
Sign up to set email alerts
|

New humanized HLA–DR4–transgenic mice that mimic the sex bias of rheumatoid arthritis

Abstract: Objective. To generate a mouse model that can mimic human rheumatoid arthritis (RA). A major difference between RA in humans and collagen-induced arthritis (CIA) in mice is the lack of sex bias and autoantibodies in the animal model. We used DRB1*0401-transgenic mice to understand the role of DR4 in susceptibility and sex bias in RA.Methods. A transgenic mouse was generated that lacked all endogenous mouse class II genes (AE o ) and expressed the RA susceptibility allele HLA-DRB1*0401. These transgenic mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 29 publications
7
100
0
2
Order By: Relevance
“…The mouse model described by Taneja et al, which is reported elsewhere in this issue of Arthritis & Rheumatism (1), is the first to share similarities with human RA. The mice lack the classic endogenous mouse class II chains.…”
Section: Maurizio Cutolomentioning
confidence: 95%
“…The mouse model described by Taneja et al, which is reported elsewhere in this issue of Arthritis & Rheumatism (1), is the first to share similarities with human RA. The mice lack the classic endogenous mouse class II chains.…”
Section: Maurizio Cutolomentioning
confidence: 95%
“…Animal models of RA provided an unequivocal platform for dissecting the cellular and molecular immune-mediated nature of inflammatory joint diseases. With the aid of animal models, the role that CD4 + T cells play in disease induction and pathogenesis was solidified using genetic modifications in strains engineered to express a specific T cell receptor (TCR) [4][5][6], as well as humanised models modified to express alleles of human MHCII that have been associated with RA [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…HLA-DR4 модель описана недавно, у мышей отсутствуют все гены II класса, но экспрессиру-ется РА-чувствительная аллель HLA-DRB1*0401 [51]. Заболевание моделируется преимуществен-но у самок.…”
Section: генетические модели раunclassified